2020
DOI: 10.21577/0103-5053.20190185
|View full text |Cite
|
Sign up to set email alerts
|

GC-MS-Based Metabolomic Profiles Combined with Chemometric Tools and Cytotoxic Activities of Non-Polar Leaf Extracts of Spondias mombin L. and Spondias tuberosa Arr. Cam.

Abstract: Agroindustrial residues, such as leaves of fruit plants, can be sources of bioactive molecules, thus adding value to co-products that are rarely explored in agroindustry. In this context, this study aimed to look into the phytochemical profiles in detail and to explore the antitumor potential of S. tuberosa and S. mombin leaves. We observed that, S. tuberosa leaf extract was cytotoxic in both tumor and healthy cells. S. mombin extracts selectively inhibited cell proliferation in the tumor cell line for prostat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…(2020) reported 9, 12 Octadecadienoic acids in n-hexane extract of Kochia indica stem. Likewise, Elufioye and Berida (2018) also reported 9, 12 Octadecadienoic acids in n-hexane extract of stem-bark and whole fruit of S. purpurea.Alpha-amyrin identified in ethanol extract of S. mombin leaves in this study have been investigated in stem-bark of Ficus exasperate(Nogueira et al, 2019) Guedes et al (2020). also reported alpha-amyrin in hexane extract of S. mombin and S. tuberose leaves.…”
supporting
confidence: 59%
See 2 more Smart Citations
“…(2020) reported 9, 12 Octadecadienoic acids in n-hexane extract of Kochia indica stem. Likewise, Elufioye and Berida (2018) also reported 9, 12 Octadecadienoic acids in n-hexane extract of stem-bark and whole fruit of S. purpurea.Alpha-amyrin identified in ethanol extract of S. mombin leaves in this study have been investigated in stem-bark of Ficus exasperate(Nogueira et al, 2019) Guedes et al (2020). also reported alpha-amyrin in hexane extract of S. mombin and S. tuberose leaves.…”
supporting
confidence: 59%
“…Twenty five (25) Squalene, one of the compounds identified in n-hexane extract of S. mombin leaves in this study was also reported in the crude ethyl acetate root extract of S. mombin by Osuntokun et al (2018). Guedes et al (2020) also reported squalene in n-hexane extract from S. tuberose and S. mombin leaves. It has been reported that squalene acts as a drug transporter by chemically linking with medicines to advance certain physicochemical properties.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In this treatment, there was a total of 27.85 ± 2.41% of cytotoxicity against murine fibroblasts in the highest concentration evaluated, in addition, the action is observed in a lower concentration (500 µg/mL). Extracts from the leaves of S. tuberosa were not able to cause toxicity, however Guedes et al (2020), demonstrated that these organs have compounds with high toxicity, since the hexane extract of the leaves showed a high toxicity against fibroblasts. This is explained by the type of solvent used in the research.…”
Section: Resultsmentioning
confidence: 97%
“…GC–MS analysis is the most suitable technique to assess plant extracts′ lipophilic profile [ 34 , 35 ]. It requires, in some cases, a derivatization procedure to convert many secondary metabolites to volatile derivatives [ 36 ], and silylation is the most recent derivatization procedure [ 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%